Os diferentes saberes utilizados na elaboração do método de análise químico mineral de Johann Andreas Cramer no século XVIII - Bortolotto, Andréa (2012)
On the one hand, this dissertation examines to what extent the Chemical knowledge and the knowledge that sprang from experiments conducted in mines contributed to a new proposal of identification and classification of minerals in the 18th century, a period in which the demand for metals expanded. On the other hand, it is an attempt to discuss the sources that were used in order to propose a new concept, which is neither a result of a simple aggregation of previous concepts nor their neglect. As a matter of fact, the new concept goes beyond that, as it entails previous knowledge by complementing and transforming it. To do so, we analyzed in what terms Johann Andreas Cramer (1710 1777) moved closer and further from the various concepts available in his time to put forth a new method of mineral assaying based on the chemical behavior of the bodies, which allowed him to identify, extract and classify minerals more precisely. Among these sources, two stand out: Georg Ernst Stahl and Herman Boerhaave, rather different sources, considered even paradoxical by many historians. Such analysis has revealed that in the History of Chemistry there were moments in which lines of thought moved away. Nonetheless, there were also moments in which they blended. That finding leads us to conclude that the History of Chemistry is to be evaluated in terms of non-continuous analysis without disregarding continuity, though